Health systems, inequality and incentives to innovate - Rajat Acharyya; María D. C. García-Alonso (University of Kent, Department of Economics, 2009)
Governments often subsidize poorer groups in society to ensure their access to new drugs. We analyze here the optimal income-based price subsidies in a strategic environment. We show that asymmetric health systems can arise even though countries are ex-ante symmetric when international price discrimination is possible. Universal access is less likely to arise without price discrimination but also health policy coordination becomes more important. This is due to the multiple equilibria which make the attainment of universal coverage within a given income range ambiguous. We also show that an increase in intra-country inequality does not always lead to less likely universal coverage when international price discrimination is possible.
Keywords: D4; L1; I1; 330; health systems; pharmaceuticals; innovation; income based subsidies; price discrimination; Gesundheitswesen; Soziale Ungleichheit; Pharmazeutisches Produkt; Innovation; Gesundheitskosten; Öffentlicher Transfer; Preisdifferenzierung; Theorie